Analysis of the Implementation of Internal Controls on Food Procurement at the Anantara Uluwatu Bali Resort Hotel - Sudarsana, I Komang Alit; Tuwi, I Wayan; Wiryanata, I Gusti Ngurah Agung (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The hospitality industry plays a vital role in supporting the tourism sector, where effective internal control systems are essential to ensure efficiency, accountability, and cost control in operational processes such as food procurement. This research explores the application of internal control in the food procurement process at Anantara Uluwatu Bali Resort, utilizing the five core components of the COSO (Committee of Sponsoring Organizations of the Treadway Commission) internal control framework. A qualitative descriptive method was employed, with data gathered through interviews, direct observations, and documentation review. The results reveal that the resort has implemented a foundational internal control system supported by organizational structures, standard operating procedures (SOPs), and an integrated information system Visual Hotel Program (VHP). Nevertheless, certain implementation gaps were identified, such as overlapping responsibilities between receiving and storekeeping functions, the lack of a formal risk assessment system, and frequent reliance on undocumented informal communication. Furthermore, the monitoring activities remain limited and are mainly carried out through informal daily briefings rather than systematic internal audits. In summary, the internal control practices within the food procurement operations at the hotel are not yet fully effective. To enhance the system's performance, improvements are needed in areas such as segregation of duties, risk identification, procedural compliance, and the establishment of routine internal monitoring mechanisms.